Pengaruh Model Pembelajaran Inkuiri Bebas Termodifikasi terhadap Keterampilan Proses Sains (KPS) Pelajaran Biologi Materi Protista dikelas X MIA 2 MAN 1 Pekanbaru Tahun Pelajaran 2021-2022 - Istiqomah Istiqomah (Bedelau: Journal of Education and Learning, 2022)
Science process skills are skills that can equip students to be able to carry out various physical activities during the discovery process as well as thinking skills and instill a scientific attitude. Students' scientific attitudes need to be trained to link knowledge with everyday life in building concepts that relate to critical thinking. The action that can be applied by the teacher is to use a modified free inquiry model. Inquiry learning provides opportunities for students to learn how to find facts, concepts and through direct experience as well as develop thinking skills and being scientific. This research is a class action research conducted in 2 cycles. The research subjects were students of class X Mia2 Man 1 Pekanbaru 2021-2022 academic year. The results showed that the indicators of science process skills that experienced the highest increase from cycle 1 to cycle 2 were the indicators of communicating, conducting experiments, observing skills, making hypotheses and interpreting skills. The advantage of inquiry learning is that all students are trained to make their own discoveries, design experiments, so that students can practice finding objects to be studied. Helps develop social skills, can interact directly both between students and with teachers, and can train courage, cooperation and can foster self-confidence